Guidance and Robust Control of a Double-Hull Autonomous Underwater Vehicle - Mendes, Carlos Hugo (2020)
The aim of this paper is to present, discuss and evaluate two linear control solutions for an Autonomous Underwater Vehicle (AUV). As guidance solution, a waypoint following and station-keeping algorithm is presented. Then a PID design is proposed, through the decoupling of the linear system into three lightly interactive subsystems. A Linear Quadratic Regulator (LQR) design is also presented, based on the division of the linear system into longitudinal and lateral subsystems. A control allocation law is also presented to deal with the underactuation problems. Both controllers proved robust for this operating point although, regarding performance, and, for the performed simulation, the LQR controller proved more responsive.